Use of E-Assessment to Support Assessment of Economic Learning during the Covid-19 Pandemic - Cholifah Punta Rinatamin; Sigit Santosa; Muhtar Muhtar (Universitas Sebelas Maret, 2021)
The closure of schools, not only disrupts teaching for students around the world but also affects assessments and causes many exams to be postponed or canceled. The purpose of this study was to determine the e-assessment media used and the barriers for teachers to carry out assessments of economic learning in secondary education units in Indonesia during the Covid-19 pandemic. This research uses descriptive analysis method. The results showed that 59.1% of teachers used google classroom as a medium for assessment and the rest used other applications in the learning assessment process. The obstacles faced include geographical conditions, device specifications, and the level of student activity. The use of this application is tailored to the needs and abilities of teachers and students in combining technology and student assessment needs.